2021
DOI: 10.1002/jmv.26851
|View full text |Cite
|
Sign up to set email alerts
|

Human polyomaviruses genomes in clinical specimens of colon cancer patients

Abstract: Colon cancer is the third cause of cancer death in the developed countries. Some environmental factors are involved in its pathogenesis, including viral infections. The possible involvement of human polyomaviruses (HPyVs) in colon cancer pathogenesis has been previously reported, leading to inconsistent conclusions. Clinical specimens were collected from 125 colon cancer patients. Specifically, 110 tumor tissues, 55 negative surgical margins, and 39 peripheral blood samples were analyzed for the presence of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…A singleplex for JCPyV and for BKPyV DNA were performed. The sequences of the primers and probes as well as the composition of the reaction mix and the thermal cycle of the Real-Time PCR have already been reported in previous publications [ 18 , 19 ]. Viral loads in urine samples and renal biopsies were expressed as copies/mL and copies/µg, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…A singleplex for JCPyV and for BKPyV DNA were performed. The sequences of the primers and probes as well as the composition of the reaction mix and the thermal cycle of the Real-Time PCR have already been reported in previous publications [ 18 , 19 ]. Viral loads in urine samples and renal biopsies were expressed as copies/mL and copies/µg, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Some evidence points to pathogens, such as viruses, as risk factors for its oncogenesis. [ 159 , 160 , 161 ]. Nevertheless, studies showed a very low prevalence (3.5%) with low and even no positivity toward viral transcripts [ 82 , 109 , 110 , 111 , 112 , 113 ].…”
Section: Merkel Cell Polyomavirus and Merkel Cell Carcinomamentioning
confidence: 99%